Fear of Covid-19 and Intentions towards Adopting E-Health Services: Exploring the Technology Acceptance Model in the Scenario of Pandemic (International Journal of Business, Economics and Management, 2021)
The aim of this paper was to investigate the link between fear of Covid-19 and individuals’ behavioral intentions toward adopting e-health services by expanding the technology acceptance model (TAM) to incorporate fear of the Covid-19 factor. To empirically testing our proposed theoretical model, we conducted a research survey in Pakistan and collected data from 624 individuals utilizing a non-probability convenience sampling strategy. The outcomes of our study declare that fear of Covid-19 are positively associated with individuals’ attitude and their subsequent behavioral intentions towards adopting e-health services. Perceived ease of use and perceived usefulness of e-health services mediated the relationship between fear of Covid-19 and individuals’ attitude towards adopting e-health services. This research is highly significant in the current scenario of Covid-19. Our study offers a theoretical model to understand why and how fear of Covid-19 is related to an individual’s intentions for adopting e-health services. Moreover, this study also extends the literature of the technology acceptance model TAM by pinpoint the impact of fear of Covid-19.